Minat Berwirausaha yang Ditinjau dari Pengaruh Pendidikan Kewirausahaan dan Motivasi Berwirausaha - Nur Anisya; Faizal Mulia; Erry Sunarya (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
This study aims to understand and examine entrepreneurial interests in terms of entrepreneurship education and entrepreneurship motivation by measuring the influence of Organizational Culture on Employee Job Statisfaction at PT. Minu Garment Sukses, and to see how much influence the quality of organizational culture on job satisfaction on employees so that results can be seen from the interests of entrepreneurship in terms of entrepreneurship education and entrepreneurial motivation both partially and simultaneously. This research uses quantitative methods with simple linear regression analysis. Taking the population in this study are all employees at PT. Minu Garment Success. The sample in this study amounted to 100 employees through a questionnaire which became an instrument for data integration. The results of the study prove that organizational culture has a positive and significant effect on job satisfaction at PT. Minu Garment Success with a significant level of 43.5% and the remaining 56.5% is determined by other factors.